Noradrenergic stimulation modulates activation of extinction-related brain regions and enhances contextual extinction learning without affecting renewal - Lissek, Silke; Glaubitz, Benjamin; Güntürkün, Onur; Tegenthoff, Martin (Frontiers in Behavioral Neuroscience, 2015)
Renewal in extinction learning describes the recovery of an extinguished response if the extinction context differs from the context present during acquisition and recall. Attention may have a role in contextual modulation of behavior and contribute to the renewal effect, while noradrenaline is involved in attentional processing. In this functional magnetic resonance imaging (fMRI) study we investigated the role of the noradrenergic system for behavioral and brain activation correlates of contextual extinction and renewal, with a particular focus upon hippocampus and ventromedial PFC, which have crucial roles in processing of renewal. Healthy human volunteers received a single dose of the NA reuptake inhibitor atomoxetine prior to extinction learning. During extinction of previously acquired cue-outcome associations, cues were presented in a novel context (ABA) or in the acquisition context (AAA). In recall, all cues were again presented in the acquisition context. Atomoxetine participants (ATO) showed significantly faster extinction compared to placebo (PLAC). However, atomoxetine did not affect renewal. Hippocampal activation was higher in ATO during extinction and recall, as was ventromedial PFC activation, except for ABA recall. Moreover, ATO showed stronger recruitment of insula, anterior cingulate, and dorsolateral/orbitofrontal PFC. Across groups, cingulate, hippocampus and vmPFC activity during ABA extinction correlated with recall performance, suggesting high relevance of these regions for processing the renewal effect. In summary, the noradrenergic system appears to be involved in the modification of established associations during extinction learning and thus has a role in behavioral flexibility. The assignment of an association to a context and the subsequent decision on an adequate response, however, presumably operate largely independently of noradrenergic mechanisms.